SHOOTING MISTAKES IN BIATHLON AS A RESULT OF INCORRECT PRONE SHOOTING POSITION - M. Klechorov (Trakia Journal of Sciences)
The present research studies the mistakes committed as a result of taking an incorrect prone shooting position in biathlon. The aim of the research is to specify the errors when taking the prone shooting position in biathlon and to analyze their possible consequences. The following methods are used to resolve the tasks of the research: analysis of the specialized literature on the topic of the research; content analysis of the shooting protocols; system and structure analysis; pedagogical observation; discussion with biathlon coaches. The research involves seventeen biathletes in the categories - women, junior women and junior men. In the course of five years a purposeful pedagogical observation was conducted on the shooting preparation of eleven elite athletes from the Bulgarian National Team of Biathlon and of six students specializing in biathlon at the National Sports Academy “V. Levski”. Results: After a detailed analysis and summary of the collected data, the acquired results describing the various types of shooting errors made by biathletes as a result of their incorrect prone position and the ways to overcome these mistakes were presented in the form of a table (Table 1.). Conclusions: The presented table could be used in the training process by coached and athletes in order to overcome the mistakes when taking the prone shooting position in biathlon.